VERIFICATION OF CAVITATION PHENOMENON AND PRESSURE INDICATORS OF ELECTRIC PUMPS - Mirzaliev, B.B. (Educational Research in Universal Sciences, 2023)
The phenomenon of cavitation in electric pumps in accordance with the pressure and flow efficiency in the elements of the pump. Examples of studying the structure of electric pumps and testing them are described.